Uric Acid Amplifies Aβ Amyloid Effects Involved in the Cognitive Dysfunction/Dementia: Evidences From an Experimental Model In Vitro. Issue 5 (16th August 2016) - Desideri, Giovambattista; Gentile, Roberta; Antonosante, Andrea; Benedetti, Elisabetta; Grassi, Davide; Cristiano, Loredana; Manocchio, Antonello; Selli, Sara; Ippoliti, Rodolfo; Ferri, Claudio; Borghi, Claudio; Giordano, Antonio; et al.
Abstract : There is still a considerable debate concerning whether uric acid is neuroprotective or neurotoxic agent. To clarify this topic, we tested the effects of uric acid on neuronal cells biology by using differentiated SHSY5Y neuroblastoma cells incubated with amyloid β to reproduce an in vitro model of Alzheimer's disease. The incubation of cells with uric acid at the dose of 40 µM or higher significantly reduced cell viability and potentiated the proapoptotic effect of amyloid β. Finally, uric acid enhanced the generation of 4‐hydroxynonenal and the expression of PPARβ/δ promoted by amyloid β, indicating a prooxidant effects. In conclusion, uric acid could exert a detrimental influence on neuronal biology being this influence further potentiated by the concomitant exposure to neurotoxic stimuli. This effect is evident for uric acid concentrations close to those achievable in cerebrospinal fluid in presence of mild hyperuricemia thus suggesting a potential role of uric acid in pathophysiology of cognitive dysfunction. These effects are influenced by the concentrations of uric acid and by the presence of favoring conditions that commonly occur in neurodegenerative disorders and well as in the aging brain, including increased oxidative stress and exposure to amyloid β. J. Cell. Physiol. 232: 1069–1078, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The study suggests that uric acid could exert detrimental effects on brain structure and function by directly influencing the viability of neuronal cells and their ability to establish synaptic connections.